Prevalence of anemia related to intestinal parasites in children and adolescents in Brazil: an integrative review - Santiago, Emanuelle de Cássia Souza (2023)
Anemia caused by lack of iron – iron deficiency anemia – is the most prevalent and it is estimated that around 90% of anemias are due to iron deficiency anemia. When the parasite lodges in the duodenal wall of the host, it starts the process of sucking blood, and ends up causing bleeding points in the mucous membranes, in addition to absorbing nutrients, which can often cause serious anemic problems. To verify, through a literature review, the prevalence of iron deficiency anemia associated with parasitic diseases in children and adolescents aged 0 to 15 years in the last 10 years in Brazil. This is an integrative literature review, in the electronic health databases indexed in the Virtual Health Library (VHL) portal, and in the Google Scholar and Periodical CAPES platforms. The articles brought data regarding the anemic condition of the children, where article 1 was the only one that did not present any anemic children, however, there were 15% of infected children. As for anemic children, it was clear that two articles showed more than 50% of infection (articles 2 and 7). Thus, it is suggestive of an association of anemia due to parasitic infections, which brings up the importance of good personal hygiene and the food consumed, in an attempt to minimize the transmission of parasites. Thus, it becomes essential to intensify health education strategies, guiding the need to promote eating habits that include iron-rich foods, proper hand and food hygiene for this public.